Frequencies of gynocoid, android and barrel shape in Malay obese attributes - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Norizan, Abdul Ghani (2017)
The prevalence of obesity has been increasing globally, with high prevalence in Malaysia. Malay obtained sedentary lifestyle besides western diet due to rapid socioeconomic growth for the last few decades. Obesity has risen to be alarming (currently 14.1%) in Terengganu, which is associated with many metabolically associated diseases including cardiovascular, metabolic dysfunctions and arterial hypertension.A total of 95 obese subjects (44.2% men, n=42, 55.8% women, n=53; Age: 19 - 60) were recruited through volunteer random sampling to be involved in a cross-sectional study. Classical anthropometric measurements (waist circumference, hip circumference, body mass index (BMI), waist to hip ratio (WHR) and body fat% were determined beside determination of a novel ASindex [hip – waist (cm)]. The Asindex was used for the determination of gynocoid, android and barrel shaped obesity in Malay obese attributes. As per methodology, the frequencies represented as percentage (fractions), are determined to be 62.1% (1:1.79) for gynocoid obesity, 6.3% (1:15.8) for android obesity and 31.5% (3:1) for barrel shape.To the best of our knowledge, this is the first report in Malaysia, reflecting the calculations derived through Asindex clearly indicating that the prevalence of gynocoid obesity is greater 89.9% of android obesity in Malay obese attributes.